Pharmacologic Aspect of Neuropathic Pain - Endang Mutiawati; Imai Indra; Syahrul Syahrul; Mulyadi Mulyadi (Syiah Kuala University, 2015)
Neuropathic pain is pain arising from nerve damage to the conductive pathways of pain (ranging from nociceptors to post central gyrus). Neuropathic pain can be caused by 1) Carcinomas, 2) Trap/compressive, 3) Congenital, 4) Immunomediated, 5) Infection, 6) Metabolic disorders, 7) nutritional deficiency, 8) Toxin, 9) Lesion, 10) Vasculitis, 11). Connective tissue disorders. To date, the pathophysiology of neuropathic pain can not be explained thoroughly, this problem leads to the treatment which has not given satisfactory results as expected. There are many types of drugs has been used for the treatment of neuropathic pain, and they are generally aimed to stop the flow of impulses in the nervous system which was activated as a result of ectopic generators in areas experiencing nerve injury. These drugs work in several locations such as: drugs that works on 'sodium channel voltage gate' (i.e Carbamazepine group), drugs that works on 'calcium channel' (i.e Gabapentin and Pregabalin), and also drugs that works on ‘the synapses gap’ (i.e Tricyclic class). Besides drugs that inhibit pain impulses propagation, the treatment of neuropathic pain also include drugs that have the ability of nervous system regeneration such as methylcobalamin group. The rationale of the use of this kind of drugs is that this drug expected to regenerate the damage of the nervous system damage which is lead to decrease the ectopic generator activity, the end result is the reducement of neuropathic pain experienced by patients